Effectiveness and safety of first-line empirical Helicobacter pylori eradication regimens in Switzerland: an interim analysis from a prospective multicentre registry (Hp-EuReg) - Michael Doulberis; Daniele Riva; Ioannis Linas; Patrick Mosler; Tom Völler; Imen Jallouli; Jürg Knuchel; Claudia Gregoriano; Pablo Gressot; Thrasyvoulos Gkretzios; Christos Kiosses; Thomas Balanis; et al. (Swiss Medical Weekly)
BACKGROUND: Helicobacter pylori infection remains prevalent globally. Despite the relatively low reported prevalence in Switzerland, the actual burden is thought to be higher, primarily due to migration. To date, limited evidence is available regarding the effectiveness of Helicobacter pylori eradication therapy in Switzerland.